BV associated bacteria specifically BVAB 1 and BVAB 3 as biomarkers for HPV risk and progression of cervical neoplasia - Kavitha Naidoo; Nathlee Abbai; Partson Tinarwo; Motshedisi Sebitloane (Hindawi Limited, 2022)
Background. Bacterial vaginosis (BV) is associated with high-risk HPV (hrHPV) genotypes. There is a proposed bidirectional relationship between hrHPV and vaginal microbial diversity. This study investigated the association between BV associated bacteria in women co-infected with Human immunodeficiency virus (HIV) and hrHPV. Methods. Stored cervical cytobrush samples were used for real time PCR detection of eight BV associated bacteria. Analysis of BV bacteria detected against HPV infection, socio-demographics and HIV data were conducted in R Statistical computing software of the R Core Team, 2020, version 3.6.3. Results. A total of 190 samples were analysed. A. vaginae (p <0.001) BVAB 1 (p <0.001), BVAB 2 (p =0.428), BVAB 3 (p <0.001), Lactobacillus species (p =0.016) and S. sanguinegens (p =0.007) were associated with prevalent hrHPV. Increasing CIN severity was independently associated with detection of BVAB 1 OR 1.51(95% CI: 0.42-5.55), BVAB 3 OR 2.72(95% CI:0.90-8.55) and S. sanguinegens OR 1.02(95% CI:0.37-2.80). All HPV genotypes/groups, gravida <2, A. vaginae (p =0.002) and BVAB 1 (p =0.026) were significantly associated with HPV persistence. BVAB 3, p =0.010 and HPV 16 were significantly associated with HPV reinfection. Conclusion. There is a significant association of A. vaginae, BVAB 1, BVAB 3, S. sanguinegens and Lactobacillus spp to prevalent hrHPV. BVAB 1, BVAB 3 and S. sanguinegens had an increased odds for increasing CIN severity. A vaginae, BVAB 1, gravida and all the HPV genotypes/groups were significantly associated with HPV persistence. Only BVAB 3 and HPV 16 were significantly associated with hrHPV reinfection at 1 year review. BVAB 1 and BVAB 3 are possible biomarkers for HPV infection and CIN progression.